Giant cell ependymoma of the cervical spinal cord: case report and review of the literature - Barbagallo, Giuseppe M. V. (Springer-Verlag, 2008)
Ependymomas account for 2–6% of all central nervous system neoplasms. They develop from the ependymal cells that line the ventricular cavities of the brain and the central canal of the spinal cord, as well as from ependymal clusters in the filum terminale. Giant cell ependymoma (GCE) is a rare subtype, with few cases reported, mostly in the brain. We describe the case of a cervical spinal cord ependymoma with pleomorphic giant cells and focal calcifications occurring in a 25-year-old woman. Magnetic resonance imaging revealed a large multicystic and partially enhancing intramedullary tumour extending from C2 to C5. Intraoperative analysis of frozen section tissue fragments suggested a malignant tumour; however, an obvious cleavage plane was present around most of the mass, and a macroscopically complete tumour removal could be achieved. Subsequently, paraffin sections and immunohistochemical investigations revealed unequivocal evidence of a GCE with focal calcifications. This case, the second giant-cell ependymoma to be described in the spinal cord and the first with focal calcifications, highlights the features of GCE and the discrepancy between the worrisome histological appearance, the surgical findings and the clinical relatively good prognosis.